2016
DOI: 10.1038/srep30643
|View full text |Cite
|
Sign up to set email alerts
|

Delivery of Hydrogen Sulfide by Ultrasound Targeted Microbubble Destruction Attenuates Myocardial Ischemia-reperfusion Injury

Abstract: Hydrogen sulfide (H2S) is an attractive agent for myocardial ischemia-reperfusion injury, however, systemic delivery of H2S may cause unwanted side effects. Ultrasound targeted microbubble destruction has become a promising tool for organ specific delivery of bioactive substance. We hypothesized that delivery of H2S by ultrasound targeted microbubble destruction attenuates myocardial ischemia-reperfusion injury and could avoid unwanted side effects. We prepared microbubbles carrying hydrogen sulfide (hs-MB) wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 40 publications
1
26
0
Order By: Relevance
“…The infarct and fibrotic area was evaluated as previously described. 18 , 20 , 23 After MI (14 and 60 days), hearts were cut into six sections and incubated in 1% triphenyl tetrazolium chloride (TTC) for 10 min at room temperature (white indicates infarct area; red indicates normal myocardium). Infarct areas were measured digitally using Image-Pro Plus 6.0 (Media Cybernetics, Bethesda, MD).…”
Section: Methodsmentioning
confidence: 99%
“…The infarct and fibrotic area was evaluated as previously described. 18 , 20 , 23 After MI (14 and 60 days), hearts were cut into six sections and incubated in 1% triphenyl tetrazolium chloride (TTC) for 10 min at room temperature (white indicates infarct area; red indicates normal myocardium). Infarct areas were measured digitally using Image-Pro Plus 6.0 (Media Cybernetics, Bethesda, MD).…”
Section: Methodsmentioning
confidence: 99%
“…45 Furthermore, the delivery of the metalloproteinase inhibitor 3 gene to the infarct region could be enhanced by using gene carrying microbubbles decorated with a matrix metalloproteinase 2 antibody, which improved cardiac function and reduced the infarct region. 19 Next to loading the microbubble shell with pharmaceutical agents and genes, the gas core can be partially replaced by therapeutic gases like hydrogen 46 or hydrogen sulfide, 47 two gases that are used to protect myocytes after myocardial ischemia-reperfusion injury. It was shown that targeted microbubble destruction substantially increased the local gas concentration and reduced the damaged tissue area after myocardial infarctions.…”
Section: Therapeutic Ceus In Cardiovascular Applicationsmentioning
confidence: 99%
“…It was shown that targeted microbubble destruction substantially increased the local gas concentration and reduced the damaged tissue area after myocardial infarctions. 46,47 Despite the significant potential of CEUS-based therapies, there is still a need to optimize treatment parameters, as many adverse events, like microvascular leakage, intracardiac hemolysis, capillary rupture, or inflammatory cell infiltration have been described in rodents. 23…”
Section: Therapeutic Ceus In Cardiovascular Applicationsmentioning
confidence: 99%
“…The optimal ratio of H2S/C3F8 was found to be 2/2 with the highest H2S-loading capacity. US-targeted hs-MB destruction controlled myocardial infarct sizes and also preserved left ventricular functions without any influence on hemodynamics or the respiratory system, thus leading to myocardial ischemia-reperfusion injury alleviation [95]. Zhu et al tested the injection of DOX in the H22 hepatocellular carcinoma (HCC)-xenografted models combined with UTMD.…”
Section: Drug/gene Deliverymentioning
confidence: 99%